DEVELOPMENT OF INTEGRATED NATURAL SCIENCE MODULES IN ISLAMIC ELEMENTARY SCHOOL IN PEKANBARU CITY - Kardina Engelina Siregar; Amril M; Hasbullah Hasbullah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
This study aims to produce Islamic integrated science module teaching materials suitable for use in class III SDIT. This research is a development research that uses the ADDIE pattern (Analyze, Design, Development, Implementation, Evaluation). Determination of the sample using purposive sampling technique. Data collection techniques by observation, interviews, validation, documentation, and learning outcomes tests. The data analysis technique used descriptive and inferential analysis. The trials were carried out in 8 SDITs in Pekanbaru city, namely SD Islam Plus YLPI Pekanbaru, SDIT Bunayya Pekanbaru, SDIT Az-Zuhra Islamic School Pekanbaru, SDIT AL-Azhar Syifa Budi Pekanbaru, SDIT Al-Rasyid Pekanbaru, SDIT Insan Utama Pekanbaru, SDIT An- Namiroh Pekanbaru, and SDIT Al-Madinah Pekanbaru class III for the 2019/2020 academic year with 80 subjects. The results showed that the developed module met the very valid category based on the validity criteria according to the assessment of the learning validator, material expert, design expert, Islamic religious education expert and teacher. Student response to the teaching materials developed was very good. Thus it can be concluded that the integrated Islamic IPA module product on the Characteristics and Needs of Living Things for Class III SDIT has very good quality in terms of validity, effectiveness and attractiveness so that it is suitable for use in the learning process